2002
DOI: 10.1086/341802
|View full text |Cite
|
Sign up to set email alerts
|

Shell Shock and Cloud Shock: Results from Spatially Resolved X‐Ray Spectroscopy withChandrain the Cygnus Loop

Abstract: We use the Chandra X-ray Observatory to analyze interactions of the blast wave and the inhomogeneous interstellar medium on the western limb of the Cygnus Loop supernova remnant. This field of view includes an initial interaction between the blast wave and a large cloud, as well as the encounter of the shock front and the shell that surrounds the cavity of the supernova progenitor. Uniquely, the X-rays directly trace the shock front in the dense cloud, where we measure temperature kT = 0.03 keV. We find kT ≈ 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 26 publications
3
35
0
Order By: Relevance
“…They found that, as a result of the interaction, the blast wave diffracts around the cloud and reestablishes ahead of it, in agreement with the observations of Fesen et al (1992). Besides, X-ray ROSAT observations (Levenson et al 1997(Levenson et al , 2002 show an indentation at this region of the Cygnus Loop followed by a compact bright knot interior to the shell, similarly to what is observed in Puppis A.…”
Section: Resultssupporting
confidence: 75%
“…They found that, as a result of the interaction, the blast wave diffracts around the cloud and reestablishes ahead of it, in agreement with the observations of Fesen et al (1992). Besides, X-ray ROSAT observations (Levenson et al 1997(Levenson et al , 2002 show an indentation at this region of the Cygnus Loop followed by a compact bright knot interior to the shell, similarly to what is observed in Puppis A.…”
Section: Resultssupporting
confidence: 75%
“…While the transmitted shock is slowed significantly as it moves into the dense shell, the reflected shock travels back through the still expanding ejecta, further heating the already shocked gas. Such a reflected shock-heating scenario has been used to explain the observed morphology at shock-cloud interaction regions in the Cygnus Loop (Levenson et al 2002).…”
Section: Thermalmentioning
confidence: 99%
“…Optical, UV and X-ray observations of SNRs show that the SN-generated shock waves travel through and interact with the denser clouds they encounter (e.g. Bocchino et al 2000;Levenson et al 2002;Patnaude et al 2002;Nichols & Slavin 2004;Levenson & Graham 2005;Miceli et al 2005), generating transmitted and reflected (bow) shocks, which, in turn, interact with each other (e.g. McKee & Cowie 1975;White & Long 1991;Poludnenko et al 2002).…”
Section: Introductionmentioning
confidence: 99%